2018
DOI: 10.1148/radiol.2018180051
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Liver Fibrosis at T1 and T2 Mapping with Extracellular Volume Fraction MRI: Preclinical Results

Abstract: Purpose To evaluate MRI T1 and T2 mapping with calculation of extracellular volume (ECV) for diagnosis and grading of liver fibrosis. Materials and Methods Different grades of fibrosis were induced in 60 male Sprague-Dawley rats by bile duct ligation (BDL) and carbon-tetrachloride (CCl) intoxication. Portal pressure was measured invasively, whereas hepatic fibrosis was quantified by hydroxyproline content, Sirius red staining, and α smooth muscle actin staining. T1 values, T2 values, and ECV were assessed by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 28 publications
4
106
0
Order By: Relevance
“…It is impossible with elastography to distinguish among these components with certainty. Specific MR sequences, like T2 mapping and T1 rho, might be helpful in discriminating fibrosis from edema in the future [30,31]. On the other hand, a composite of hepatic congestion and fibrosis measures might be important, clinically, in the longitudinal follow-up of Fontan liver disease [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is impossible with elastography to distinguish among these components with certainty. Specific MR sequences, like T2 mapping and T1 rho, might be helpful in discriminating fibrosis from edema in the future [30,31]. On the other hand, a composite of hepatic congestion and fibrosis measures might be important, clinically, in the longitudinal follow-up of Fontan liver disease [32].…”
Section: Discussionmentioning
confidence: 99%
“…Double contrast-enhanced MRI using gadolinium-based CAs and SPIOs with or without texture analysis has been used to differentiate early liver fibrosis from advanced disease with excellent results [23,54,55]. Collagen fiber deposition in the space of Disse leads to an increase of the extracellular space quantifiable as the distribution volume fraction of nonspecific CA in the parenchymal (equilibrium) phase by MRI (or CT) [56][57][58][59]. Preclinical studies have shown that the liver accumulation of collagen targeted CAs correlates with histological fibrosis scores [60].…”
Section: Mrementioning
confidence: 99%
“…Calculation of the ECV normalized for hematocrit using an extracellular contrast agent was described elsewhere 9,11,13,14 : www.nature.com/scientificreports/ For hepatocyte specific contrast agents, one may assume a low-level equilibrium between intravascular und extracellular compartment, and a mainly intracellular storage. An illustration can be found in Fig.…”
Section: Calculation Of Intracellular Accumulation Capacitymentioning
confidence: 99%